FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIK USAHA KECIL MENENGAH DALAM MELAPORKAN KEWAJIBAN PERPAJAKAN DI KECAMATAN TAMALATE KOTA MAKASSAR - Rusdiah Rusdiah (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
This study aims to determine a) the effect of knowledge of the taxpayer for the small and medium enterprises in the city of Makassar, b.) An understanding of self the assessment on small and medium enterprises in the city of Makassar, c) the level of income of the taxpayer on small and medium enterprises in Makassar , d) the level of convenience in making a payment system of taxation to reporting tax obligations on small and medium enterprises sector in Makassar Tamalate District, analytical methods used are descriptive statistics were used to describe or give a picture of the object studied. The population in this study is small and medium businesses that exist Tamalate District Makassar. The results showed that, a) Knowledge taxpayer affect the reporting of tax obligations on small and medium enterprises sector in Makassar. b) understanding of self-assessment system does not significantly affect the reporting of tax obligations on small and medium enterprises sector in the City Makassar.c) The level of income of the taxpayer does not significantly affect the reporting of tax obligations on the small business sector and menenga in Makassar, .d ) Ease of doing the payment system of taxation significantly affect the reporting of tax obligations on small and medium enterprises sector in Makassar.